Principles of criminal procedure: Post - investigation - Lafave, Wayne R (Thomson,West Academic Publishing, 2004)
This book, for use in connection with a course focused upon the formal part of the criminal process, covers counsel, bail, the charging decision, preliminary hearing and grand jury review, the prosecution's location and scope, speedy trial, pleading and discovery, guilty pleas, jury trial, pretrial publicity, the trial, double jeopardy, sentencing, appeal, and collateral attack. All sections in the book are cross-referenced to comparable sections of the authors' seven-volume Criminal Procedure treatise containing more detailed analysis and citations to additional supporting authorities